Disability Acceptance in Asian Societies: A Literature Review of Culture and Philosophy - Zaskia Andini Ramli; Zahra Wirani (Universitas Muhammadiyah Palu, 2025)
This study explores how disability acceptance in Asian society through a literature review approach based on cultural and philosophical perspectives. This article reviews 17 research journal articles spread from various countries including Indonesia, Singapore, Thailand, Vietnam and Brunei Darussalam. This article finds that disability acceptance is not only shaped by the legal system, but also heavily influenced by local norms, culture, religion and even language. These findings highlight how the stigma of disability is persistent in a belief in karma, a culture of shame and a meritocratic ideals that make acceptance of disability conditional. The research articles were reviewed using the help of NVIVO 12 software to conduct thematic analysis, by identifying themes based on sociocultural, religious and philosophical that shape the acceptance of disability in the societies of various countries in Asia. This article also found that the model of social acceptance for people with disabilities has shifted, from a paternalistic to a humanistic model that focuses on the dignity and diversity of the human body. This article contributes to inclusive issues in society by offering the importance of culture, policy and also community in encouraging disability acceptance.